Saccostrea scyphophilla ... - Wells, Fred E.; Lukehurst, Sherralee S.; Fullwood, Laura A. F.; Harvey, Euan S. (Zenodo, 2024)
Saccostrea scyphophilla (Peron and Lesueur, 1807) (Figures 2b, 3; Table 1) Brief description of shell: Shell large, up to 10cm in length, very heavy. Usually occurs as individuals that in dense assemblages do not extend over each other. Upper surface rounded. Shell off white, margins purplish. Interior whitish, adductor muscle scar on right valve may be a deep purple. Records in the present survey: Ashburton Port area: Direction Island; East end Thevenard Island; Ashburton Island; Salt Creek; Old Onslow jetty, Beadon Point. Dampier Port area: Withnell Bay; Southern entrance to King Bay; Norbill Bay, Rosemary Island; Whalers Bay, Malus Island; Marney Bay, Malus Island; High Point, Whittaker Island; North side of East Intercourse Island. Port Hedland Port area: Public boat ramp; Finucane Island. Previous records in the Pilbara verified by DNA sequences: Lam and Morton (2006): Vlamingh Head, north of Exmouth; Barrow Island; Withnell Bay, Burrup Peninsula (all as S. mordax (Gould, 1850). Snow et al. (2023): ... : Published as part of Wells, Fred E., Lukehurst, Sherralee S., Fullwood, Laura A. F. & Harvey, Euan S., 2024, Distribution of intertidal rock oysters in the Pilbara, Western Australia, pp. 131-143 in Management of Biological Invasions 15 (1) on pages 137-138, DOI: 10.3391/mbi.2024.15.1.08, http://zenodo.org/record/12628087 ...